Sowing uniformity of bed-type pneumatic maize planter at various seedbed preparation levels and machine travel speeds - Ahmad, Fiaz; Adeel, Muhammad; Qui, Baijing; Ma, Jing; Shoaib, Muhammad; Shakoor, Amir; Chandio, Farman Ali (International Journal of Agricultural and Biological Engineering, 2021)
Precision planters are important machines in the regime of modern technological agriculture. Field conditions, seed metering system and machine operating parameters affect the pneumatic planter performance. The pneumatic planter was evaluated to determine the effect of three tillage levels (L1, L2, and L3) and four travel speeds (S1, S2*, S3 and S4). The sowing uniformity of the planter was observed with respect to the horizontal distribution of seeds within a row and described by using the precision index (Ip), the multiple index (Imult), the miss-seeding index (Imiss) and the quality of feed index (Iqf). The results revealed that the tillage levels (L) and travel speed (S) had a significant effect (p<0.05) on dependent variables. The maximum Imiss (22.12%) was observed at L1 and S4 whereas the maximum Imult was observed at L1 and S1. The mean values of missing-, multi-, quality- feed and precision indices were 5.14%, 5.833%, 89.03% and 17.85% at L3, respectively. The mean values of multi-index 17.59%, 14.44%, 12.40% and 10.18%, quality feed index 74.07%, 75.92%, 75.74% and 74.07% and precision indices 21.47%, 23.26%, 25.51% and 28.53% were at S1, S2, S3 and S4, respectively. The study showed that maize could be seeding within an acceptable precise range by bed-type pneumatic planter subjected to the proper seedbed preparation level. Keywords: sowing uniformity, pneumatic planter, tillage levels, travel speed DOI: 10.25165/j.ijabe.20211401.5054 Citation: Ahmad F, Adeel M, Qiu B J, Ma J, Shoaib M, Aamir S, et al. Sowing uniformity of bed-type pneumatic maize planter at various seedbed preparation levels and machine travel speeds. Int J Agric & Biol Eng, 2021; 14(1): 165–171.